2022
DOI: 10.1029/2021gl096606
|View full text |Cite
|
Sign up to set email alerts
|

On the Association of the Summertime Shortwave Cloud Radiative Effect in Northern Russia With Atmospheric Circulation and Climate Over East Asia

Abstract: This study employs ERA5 reanalysis and CERES/EBAF Ed4.1 data to evaluate the dominant features of summer shortwave cloud radiative effect (SWCRE) variability and associated atmospheric circulation anomalies. Our findings suggest that the greatest variability in summer SWCRE occurs over the Barents, Kara, and Laptev seas and northern Eurasia. We also observe a close relationship between summertime SWCRE, particularly in northern Russia, and atmospheric circulation variability over East Asia. Significant positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In this case, optically thick clouds increase the planetary albedo and, thus, the amount of shortwave radiation reflected back to space. In summer, the effects on the shortwave radiation may outweigh those with respect to the longwave fluxes, resulting in a cooling of the surface (Kay & L'Ecuyer, 2013; Betts et al., 2014; Vihma et al., 2016; Chernokulsky & Esau, 2019; Liu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, optically thick clouds increase the planetary albedo and, thus, the amount of shortwave radiation reflected back to space. In summer, the effects on the shortwave radiation may outweigh those with respect to the longwave fluxes, resulting in a cooling of the surface (Kay & L'Ecuyer, 2013; Betts et al., 2014; Vihma et al., 2016; Chernokulsky & Esau, 2019; Liu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, optically thick clouds increase the planetary albedo and, thus, the amount of shortwave radiation reflected back to space. In summer, the effects on the shortwave radiation may outweigh those with respect to the longwave fluxes, resulting in a cooling of the surface (Kay & L'Ecuyer, 2013;Betts et al, 2014;Vihma et al, 2016;Chernokulsky & Esau, 2019;Liu et al, 2022). Simulations with Earth system models (ESM) and numerical weather prediction models have shown the summertime CC over continental regions to be sensitive to the soil-and surface hydrology (de Vrese et al, 2023;Kim et al, 2020;Krinner, 2003;Lawrence & Slater, 2007;Qiao et al, 2023;Subin et al, 2012;Vecellio et al, 2019), as the latter determine the amount of water available for evaporation and transpiration.…”
Section: Introductionmentioning
confidence: 99%
“…Arctic warming may induce a weakened equator-to-pole thermal gradient, which is associated with the weakening of mid-latitude circulation, leading to more persistent hot-dry extremes in the mid-latitudes [24]. On the other hand, the reduction in Arctic sea ice is conducive to triggering the Rossby wave, which originates from the Arctic and propagates eastward, then disperses southward toward East Asia, causing extreme droughts there in the summer [25,26]. However, it remains unclear whether changes in the AD anomaly can influence contemporaneous climatic variability in Eurasia via internal atmospheric variability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to Arctic warming, sea ice has decreased rapidly (Kwok et al 2009;Maslanik et al 2011) since the beginning of 21st century, which was found to have an important impact on rainfall in east Asia through its impacts on mid-latitude circulations (Nakamura and Sato 2022;He et al 2018). Liu et al (2022) pointed out that positive summer shortwave cloud radiative anomalies over northern Russia favor the generation of the Ural blocking, and trigger the positive Eurasian pattern, resulting in an increase of precipitation in northern China. The previous studies have discussed the factors that influence summer extreme precipitation in North China, and pointed out the possible impacts from WPSH and middle and high latitude circulations under global warming.…”
Section: Introductionmentioning
confidence: 99%